THINK PAIR SHARE (TPS) STRATEGIES AND DIRECTED READING THINKING ACTIVITY (DRTA) TO IMPROVE STUDENTS’ MOTIVATION ON READING COMPREHENSION ACHIEVEMENT - Diana Surbakti; Jumino Suhadi; Andang Suhendi (JOURNAL OF LANGUAGE, 2022)
The research deals with teaching strategies and students’ motivation on reading comprehension achievement. The objective of this study is to reveal that the students’ achievement in reading comprehension taught by Think Pair Share is significantly higher than that taught by Directed Reading Thinking Activity using question answer relationship teaching study. The research method used is quantitative research design. The populations of this research are the students of Midwifery Grade II  at STIKes Mitra Husada Medan, Academic year 2021/2022. Two classes are randomly selected and the total samplings are 72 students. The instruments used are multiple choice test and questionnaire. The data analyzed are by Two-Way ANOVA with 2x2 factorial designs with F observed = 14.1 and F table = 4.00, and the results indicated the Fobserved Ftable, so null hypothesis (Ho) was rejected. It is concluded that the students taught by using TPS strategy is better than those taught by using Directed Reading Thinking Activity on reading comprehension achievement. Based on this research, researchers recommend using TPS learning model because this learning model can improve students' ability to solve reading comprehension problems. This model  can also be used as an alternative to apply innovative English learning, especially in reading, creating an exciting learning atmosphere, and also providing opportunities for students to express their ideas in English in their own way.